System of Dental Care Services For Children at The Community Health Center in Lawang Gintung Bogor - Milana Yo; Sri Sundari; Bambang Rismadi; Marisi Pakpahan; Ratnawati Prayogi (International Journal of Economics and Management Sciences, 2024)
Dental and oral health is a vital aspect of overall health that supports functions such as digestion, speech, chewing, and enhancing an individual's self-esteem and quality of life. Currently, the rate of follow-up visits by elementary school students in the Lawanggintung Health Center area remains low, leading to unmet indicators for dental services. The main issue is that students do not adhere to their scheduled dental care appointments and are permitted to seek treatment at other healthcare facilities. This study aims to analyze the role of the health center in addressing dental health issues among children in schools and to investigate the efforts made by the health center for elementary school students who have not received dental treatment. The research method employed is qualitative with a descriptive approach, utilizing interviews, observations, and documentation. The findings indicate that the health center's role in managing children's dental health issues at schools is reasonably effective through promotive, preventive, and curative efforts. The initiatives for elementary school students who have not received dental treatment mainly include referrals, providing feedback to parents and school authorities, as well as health education.